Pricing Strategy of Sudut Pajak Website Service at Politeknik Negeri Batam - Anggraini, Ria; Arniati, Arniati; Rahmawati, Diah Putri (Pusat P2M Politeknik Negeri Batam, 2024)
This research aims to explore the pricing strategies for tax services offered on the Sudut Pajak website at Politeknik Negeri Batam. The study combines the aspects of the SBIFT model